2015
DOI: 10.1038/ncomms7096
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis and antiviral activity of indolosesquiterpenoids from the xiamycin and oridamycin families

Abstract: Indolosesquiterpenoids are a growing class of natural products that exhibit a wide range of biological activities. Here, we report the total syntheses of xiamycin A and oridamycins A and B, indolosesquiterpenoids isolated from Streptomyces. Two parallel strategies were exploited to forge the carbazole core: 6π-electrocyclization/aromatization and indole C2–H bond activation/Heck annulation. The construction of their trans-decalin motifs relied on two diastereochemically complementary radical cyclization reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(58 citation statements)
references
References 76 publications
0
55
0
2
Order By: Relevance
“…For this purpose, after the sequential exposure of 4 to potassium tert ‐butoxide and triethylborane (allowing the formation of an indolyltriethylborate species), farnesyl bromide ( 8 ) served as the electrophile (Scheme ) . Under these conditions, complexation of the indole anion is supposed to enhance the C‐3 nucleophilicity by electron enrichment, therefore allowing the C‐3 quaternization.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, after the sequential exposure of 4 to potassium tert ‐butoxide and triethylborane (allowing the formation of an indolyltriethylborate species), farnesyl bromide ( 8 ) served as the electrophile (Scheme ) . Under these conditions, complexation of the indole anion is supposed to enhance the C‐3 nucleophilicity by electron enrichment, therefore allowing the C‐3 quaternization.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we accomplished the total syntheses of a series of naturally occurring indole terpenoids (Scheme A) . From a retrosynthetic point of view, indole terpenoid scaffolds can be disassembled into indole (highlighted in red, Scheme A) and terpenoid (highlighted in blue, Scheme A) motifs in general ,,. Thus, structurally diverse indole terpenoid mimics can be directly prepared from simple indole and terpenoid building blocks (Scheme B), if efficient cross‐coupling‐type reactions are available for forming the linkage bonds (highlighted in cyan, Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…[37] The Pd(OAc) 2 /PhI(OAc) 2 /AcOH/Ac 2 O procedure has been used for acetoxylation of the O-benzyl and O-methyl oximes shown in Equations (12) and (13), in steps towards the total synthesis of paspaline [Equation (12)] [38] and oridamycins [Equation (13)]. [39,40] Pd-catalyzed benzoyloxylation of an ortho-benzylic methyl group of 2,4,6-trimethylbenzaldehyde O-methyl oxime has been carried out with use of a mixture of PhI(OAc) 2 and m-O 2 NC 6 H 4 CO 2 H in toluene under oxygen [Equation (14)]. [41] An exchange reaction leading to (m-O 2 NC 6 H 4 CO 2 ) 2 PhI as the reagent could be involved.…”
Section: )-H Functionalizationmentioning
confidence: 99%
“…Although it was recently reported that N-(3-methylheptan-3yl)acetamide was reluctant to undergo acetoxylation under Pd(OAc) 2 /PhI(OAc) 2 /AcOH conditions [Equation (40)], [59] To differentiate these sides, we use the terms "CO-side" and "Nside" with α or and α′, ′, γ′ or δ′ for the C-H positions of the respective sides, as depicted in Scheme 14. Hydrolysis or alcoholysis of the Pd-catalyzed reaction products affords acids, esters, or amines bearing C(sp 3 )-OR groups.…”
Section: Carboxamidesmentioning
confidence: 99%